Role of the Dopamine Transporter in the Action of Psychostimulants, Nicotine, and Other Drugs of Abuse - Zhu, J.; Reith, M. E.A. (CNS & Neurological Disorders - Drug Targets, 2008)
A number of studies over the last two decades have demonstrated the critical importance of dopamine (DA) in the behavioral pharmacology and addictive properties of abused drugs. The DA transporter (DAT) is a major target for drugs of abuse in the category of psychostimulants, and for methylphenidate (MPH), a drug used for treating attention deficit hyperactivity disorder (ADHD), which can also be a psychostimulant drug of abuse. Other drugs of abuse such as nicotine, ethanol, heroin and morphine interact with the DAT in more indirect ways. Despite the different ways in which drugs of abuse can affect DAT function, one evolving theme in all cases is regulation of the DAT at the level of surface expression. DAT function is dynamically regulated by multiple intracellular and extracellular signaling pathways and several protein-protein interactions. In addition, DAT expression is regulated through the removal (internalization) and recycling of the protein from the cell surface. Furthermore, recent studies have demonstrated that individual differences in response to novel environments and psychostimulants can be predicted based on individual basal functional DAT expression. Although current knowledge of multiple factors regulating DAT activity has greatly expanded, many aspects of this regulation remain to be elucidated; these data will enable efforts to identify drugs that might be used therapeutically for drug dependence therapeutics.
Keywords: amphetamine